Biofouling community composition across a range of environmental conditions and geographical locations suitable for floating marine renewable energy generation. Issue 3 (15th March 2016) - Macleod, Adrian K.; Stanley, Michele S.; Day, John G.; Cook, Elizabeth J.
Abstract: Knowledge of biofouling typical of marine structures is essential for engineers to define appropriate loading criteria in addition to informing other stakeholders about the ecological implications of creating novel artificial environments. There is a lack of information regarding biofouling community composition (including weight and density characteristics) on floating structures associated with future marine renewable energy generation technologies. A network of navigation buoys were identified across a range of geographical areas, environmental conditions (tidal flow speed, temperature and salinity), and deployment durations suitable for future developments. Despite the perceived importance of environmental and temporal factors, geographical location explained the greatest proportion of the observed variation in community composition, emphasising the importance of considering geography when assessing the impact of biofouling on device functioning and associated ecology. The principal taxa associated with variation in biofouling community composition were mussels ( Mytilus edulis ), which were also important when determining loading criteria.